MODEL DAT DALAM PEMBELAJARAN KITAB KUNING DI PESANTREN - Apdoludin Apdoludin; Mujiyono Wiryotinoyo (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
This article describes a model Debate Analysis and Findings (DAT) in the yellow book learning in schools to improve students' critical thinking skills so they can find a new science. This article is an article the development model of learning called DAT models. DAT models applied by using two parallel classes, two classes as the control group and three other classes as the experimental group. In a grade control applied to the conventional learning model and the experimental class applied DAT models. Through the model DAT teachers are expected to be helped in the classroom so that learning takes place more systematically implemented and significantly improved comprehension and critical thinking skills of students.Keywords: debate, analysis, findings, boarding, yellow book